2020
DOI: 10.48550/arxiv.2010.13605
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Linear turnpike theorem

Abstract: The turnpike phenomenon stipulates that the solution of an optimal control problem in large time, remains essentially close to a steady-state of the dynamics, itself being the optimal solution of an associated static optimal control problem. Under general assumptions, it is known that not only the optimal state and the optimal control, but also the adjoint state coming from the application of the Pontryagin maximum principle, are exponentially close to a steady-state, except at the beginning and at the end of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…[46,Theorem 1]). The passage from local to global estimates seems to be possible [44,43] under some extra assumptions, such as the existence of a storage function, but this comes at the price of losing quite some information on the multiplicative constants appearing in (1.20). Moreover, the condition T > 1 κ log C d,α,β,γ + 2δ of Theorem 1.7 should be replaced with a condition of the form T > T 0 with T 0 depending on the initial conditions and potentially very large.…”
Section: Introduction and Statement Of The Main Resultsmentioning
confidence: 99%
“…[46,Theorem 1]). The passage from local to global estimates seems to be possible [44,43] under some extra assumptions, such as the existence of a storage function, but this comes at the price of losing quite some information on the multiplicative constants appearing in (1.20). Moreover, the condition T > 1 κ log C d,α,β,γ + 2δ of Theorem 1.7 should be replaced with a condition of the form T > T 0 with T 0 depending on the initial conditions and potentially very large.…”
Section: Introduction and Statement Of The Main Resultsmentioning
confidence: 99%
“…Strict dissipativity is a rather strong assumption for ensuring the measure turnpike property, which, as said above, is rather weak when compared to the exponential turnpike property. But actually, under the assumption of strict dissipativity, in [169] it is shown that for almost every s ∈ (0, 1), y T (sT ) → y and u T (sT ) → u as T → +∞, which is a significantly stronger result. In fact, it can be said that, in some sense, the turnpike property is engraved within the notion of strict dissipativity.…”
Section: P =mentioning
confidence: 98%
“…Therefore, necessarily, u 1 < 0 and u 2 > 0, whence the constraints in (9. The above non-uniqueness result has since been extended to more abstract settings by means of techniques using convexity properties of Chebychev sets ( [36]), and has also been explored for finite-dimensional control systems in [169]. We further discuss the latter in Section 15.…”
Section: Theorem 810 ([145]mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed beginning with [1] there has been widespread interest in dissipativity notions of OCPs in context of model predictive control, see [5,9,7]. The driving force behind these investigations is the close relation between disspativity and turnpike properties of OCPs [10,7,25]…”
Section: Dissipativity Turnpike and Steady Statesmentioning
confidence: 99%